Online fundraising for NPOs via email marketing – A critical success factors analysis in Germany, Austria, and Switzerland - Sonja Harken; Vanessa Mertins; Michael Urselmann (International Review on Public and Nonprofit Marketing, 2023)
This study aims to empirically determine success factors in the email marketing as a sub-discipline of online fundraising of nonprofit organizations (NPOs). Hereby, it responds to the gap of knowledge as existing research has not in detail touched nonprofit email marketing. To explore success factors in NPOs' email marketing, a detailed structural equation model, in which email marketing success acts as the final endogenous variable and the nine potential success factors function as formative latent exogenous variables, was developed. A quantitative survey was conducted with employees of NPOs from German-speaking countries. For data analysis, which was carried out with the software SmartPLS, 153 responses were utilized. Using aggregate and disaggregate analyses on the developed model, various critical success factors in NPOs' email marketing could be empirically identified. Furthermore, an importance-performance map analysis allowed the identification of the most crucial measures for increasing success, as a low performance of the NPOs faces a high total effect on email marketing success. From the results of the importance-performance map analysis, it was possible to derive specific practice-relevant action recommendations regarding measures in which NPOs should prioritize an increase in performance. Therefore, in addition to its theoretical relevance, the study also has a strong practical value.
Keywords: 380; Digital fundraising; Email marketing; Online fundraising; Nonprofit marketing; Structural equation model; Importance-performance map analysis; Critical success factor analysis